Formação inicial de professores e as Tecnologias Digitais da Informação e Comunicação: busca de padrões orientadores - Silva, Selma Colonna de Oliveira (2014)
This research aims to identify the fundamentals of TDIC proposed standards in relevant training initiatives, recorded in the literature, and how such proposals are reflected in the curriculum of teacher education. To do so, we developed a documentary research study which required a specific methodological approach to the construction of its analysis parameters. This trend had distinct phases of collection, selection and analysis of information, both for the development of analytical tools (scripts) as to the actual analysis of the data collected by these instruments and their results. In a first phase, the corpus of the research were the training standards present in eight national and international initiatives whose analysis consisted of preliminary parameters at a later stage, to identify the existence of patterns in TDIC present in curricular programming degree courses in pedagogy of São Paulo State universities. In addition, these parameters, we designed a set of six dimensions of analysis of TDIC skills that can be addressed in initial teacher training, which included the theoretical contributions of Millman & Darling-Hammond (1997), Tuijnman & Postlethwaite (1994) , Ravitch (1996), Reigeluth (1997), Gros & Silva (2004), Piccioto (2005), Costa (2010), Almeida (2009, 2011), Almeida and Valente (2011) and Novaes (2013), among others. In the result set of analyzes, it was possible to identify that the current setting of curricula, there is an impossibility of adopting training standards TDIC because the vast majority of subjects, dealing specifically with the pedagogical use of TDIC, are optional and also by permanence of designing a curriculum more instrumental than integrative of TDIC in pedagogical practice